2022
DOI: 10.1186/s42825-022-00092-5
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of a novel tanning agent from indigenous plant bark and its application in leather processing

Abstract: The use of vegetable tanning materials in leather processing has drawn attention as an alternative to basic chromium sulphate for its natural abundance and environmental aspects. In this work, an attempt has been made to extract vegetable tannins from Xylocarpus granatum bark using different solvents (e.g., water, methanol, ethanol, and chloroform) and compare with conventional vegetable tanning agents such as mimosa and quebracho. The highest extraction efficiency was observed 31.22% by methanol. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
0
30
1
Order By: Relevance
“…Extract of X. granatum bark (vegetable tanning agent) was prepared using 100% methanol by rotary evaporator in a previous study of the same author and found 31.22% extraction efficiency of tannin [22]. The extracted tannin was found to be a condensed type of tannin whereas the Xylocarpus granatum bark tannin contained 48% of condensed tannin [22]. It was applied in leather to produce semi-chrome and chrome retanned leather for evaluating their necessary properties.…”
Section: Application Of Extracted Tanning Materials (X Granatum Bark)...mentioning
confidence: 99%
“…Extract of X. granatum bark (vegetable tanning agent) was prepared using 100% methanol by rotary evaporator in a previous study of the same author and found 31.22% extraction efficiency of tannin [22]. The extracted tannin was found to be a condensed type of tannin whereas the Xylocarpus granatum bark tannin contained 48% of condensed tannin [22]. It was applied in leather to produce semi-chrome and chrome retanned leather for evaluating their necessary properties.…”
Section: Application Of Extracted Tanning Materials (X Granatum Bark)...mentioning
confidence: 99%
“…Quercus species, commonly known as “oaks”, belong to the group of the most exploited deciduous trees, which are a source of wood for the manufacture of furniture as well as for fuel. The main waste resulting from the primary processing of oak is represented by its bark, which is mostly used as an alternative fuel or tanning agent in the leather industry [ 6 , 7 ]. Moreover, the bark of different oak species is cited as a herbal product with long-term documented use in human and veterinary medicine, especially for their tannin-rich content correlated with astringent, hemostatic, antibacterial, or antidiarrheal properties [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several organic tannins extracted from plants have been used as organic tanning agents, including tannins extracted from Tessmannia burttii Harms. Xylocarpus granatum produces leather with good thermal stability and has been reported as an eco-friendly source of veg tannins for a chromium-free process. , Glutaraldehyde is the most commonly used aliphatic aldehyde in the tanning process. Still, its usage is restricted because of free aldehydes, potential carcinogenic agents that cause oxidative cell damage in living cells.…”
Section: Introductionmentioning
confidence: 99%